Evaluación de dos tipos de gonadotropina corionica equina comerciales sobre la tasa de preñez y niveles de progesterona en vacas cebuinas - Mecías Acosta, Ángel Ignacio (2021)
The objective of the research was to evaluate two types of commercial equine chorionic gonadotropin (eCG) on the reproductive parameters in zebu cows with calves at the foot. 360 adult zebu cows were used with calf at the foot distributed in three groups: 120 cows treated with Novormon® (eCG 1), another 120 cows with Sincro eCG® (eCG 2) and the remaining 120 cows were considered as Control group (without treatment with eCG). The cows had an average weight of 440 ± 40 kg and body condition between 2.5 to 4; received a traditional synchronization treatment with progesterone and estradiol. The data were processed by means of the general and mixed linear models procedure by means of InfoStat, with logit link, an alpha <0.05 was used to determine significant differences. It was found that the pregnancy rate was higher in the cows with Novormon® (62.50%) and Sincro eCG® (60.00%) compared to the control group (39.16%; P = 0.001). In addition, progesterone levels were similar in both synchronization groups (5.9 ng / mL and 5.5 ng / mL, respectively) but higher compared to the control group (3.2 ng / mL; P = 0.02). . It is concluded that the use of both equine chorionic gonadotropins (Novormon® and Sincro eCG®) allow a similar pregnancy rate to be obtained and that their use is important to achieve greater reproductive performance.